FEATURES OF FORMING OF LIBRARY FUND OF INSTITUTION OF HIGHER LEARNING FOR QUALITY PROVIDING OF EDUCATION - Kovtunenko, Natalia A. (University Library at a New Stage of Social Communications Development. Conference Proceedings, 2019)
The questions of forming of educational library fund are considered. Forming principles and their using are certain for completing of library fund of institution of higher learning. The necessity of updating of library funds is shown institutions of higher learning for providing of the quality educating.